2022
DOI: 10.1007/s10856-022-06673-4
|View full text |Cite
|
Sign up to set email alerts
|

Design of an electrospun tubular construct combining a mechanical and biological approach to improve tendon repair

Abstract: Hand tendon injuries represent a major clinical problem and might dramatically diminish a patient’s life quality. In this study, a targeted solution for flexor tendon repair was developed by combining a mechanical and biological approach. To this end, a novel acrylate-endcapped urethane-based polymer (AUP) was synthesized and its physico-chemical properties were characterized. Next, tubular repair constructs were developed using electrospinning of the AUP material with incorporated naproxen and hyaluronic acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Mechanical testing of isolated sheep tendons has shown that the minimum limiting stresses required for flexor tendon repair were fully met. The incorporation of anti-inflammatory and antiadhesive compounds has a minimal inflammatory response and adhesion to surrounding tissues to minimize scar tissue formation and improve the rate of collagenization [ 63 ]. An electrospinning tube, as a kind of product to wrap the injured part of tendon, has the application potential of preventing peritendinous adhesion and repairing.…”
Section: Functional Electrospinning Products Of 3d Structures For Ten...mentioning
confidence: 99%
“…Mechanical testing of isolated sheep tendons has shown that the minimum limiting stresses required for flexor tendon repair were fully met. The incorporation of anti-inflammatory and antiadhesive compounds has a minimal inflammatory response and adhesion to surrounding tissues to minimize scar tissue formation and improve the rate of collagenization [ 63 ]. An electrospinning tube, as a kind of product to wrap the injured part of tendon, has the application potential of preventing peritendinous adhesion and repairing.…”
Section: Functional Electrospinning Products Of 3d Structures For Ten...mentioning
confidence: 99%
“…Pien et al fabricated a PCL NF tubular structure by electrospinning based on a columnar collector and cocultured tenocytes and MSCs on the tubular NFM for constructing a tendon construct. [144] To develop a thick tissue construct with an anisotropic structure, the stacking method has been adopted using aligned 2D NFMs. Kim et al fabricated a skin-muscle tissue construct by staking HUVECs, human foreskin dermal fibroblasts, and skeletal muscle (C2C12) cell layers, which were individually cultured on the aligned PCL NFMs (Figure 13b).…”
Section: Construction Of Biomimetic Organ/tissue Constructmentioning
confidence: 99%
“…fabricated a PCL NF tubular structure by electrospinning based on a columnar collector and cocultured tenocytes and MSCs on the tubular NFM for constructing a tendon construct. [ 144 ]…”
Section: Application Of Nfm Fabrication Techniques For Construction O...mentioning
confidence: 99%
“…The mechanical properties have been improved, but the tendon adhesions and inflammation problems still need further improvement, and for these two persistent problems, Pien et al . [ 121 ] offers a new idea. To fabricate tubular repair constructs, naproxen and hyaluronic acid (i.e.…”
Section: Electrospun Fiber Materials For Tendon Repairmentioning
confidence: 99%